Cystoscopic hydrodistention characteristics provide clinical and long-term prognostic features of interstitial cystitis after treatment - Yu, Wan-Ru (Sci Rep, 2021)
To evaluate the correlations of clinical symptoms, urodynamic parameters, and long-term treatment outcomes with different findings of cystoscopic hydrodistention (HD) in patients with interstitial cystitis/bladder pain syndrome (IC/BPS). This retrospective analysis of 486 patients with IC/BPS investigated baseline clinical symptoms, disease duration, medical comorbidities, urodynamic findings, cystoscopic characteristics [including maximal bladder capacity (MBC) and the presence of glomerulations and Hunner’s lesions], and outcomes according to the five IC/BPS HD subtypes based on the glomerulation grade, MBC, and the presence of Hunner’s lesions. Receiver operation characteristic analysis identified an optimal cutoff value of MBC ≥ 760 ml as a predictor of satisfactory outcomes. Glomerulation grade and MBC were significantly correlated (r =  − 0.403, P < 0.001), and both were significantly associated with IC Symptom Index scores. The rate of satisfactory outcomes was better for the patients with low glomerulation grade and MBC ≥ 760 ml (64.2%), and significantly worse for those with Hunner’s lesions (36.8%); no significant differences were noted among the other groups. The results suggested that IC/BPS patients can be classified into the following three distinct subgroups: (1) those with low glomerulation grade and MBC ≥ 760 ml; (2) those with low glomerulation grade and MBC < 760 ml, or with high glomerulation grade regardless of MBC; and (3) those with Hunner’s lesions. The results showed that three IC/BPS subgroups had distinct bladder characteristics and treatment outcomes. The patients with high MBC and low glomerulation grade after HD had more medical comorbidities but a significantly higher rate of satisfactory treatment outcome. IRB: 105-25-B.